Comparison of Biuret and soybean meal for wintering cows on bluestem pasture II. Effect on birth and weaning weight of progeny - Thyault, H.A.; Harbers, L.H.; Smith, E.F. (Kansas State University. Agricultural Experiment Station, 2011)
During the winter of 1969-70, 48 five-year-old cows were divided into three groups to compared soybean meal with biuret as a winter supplement in combination with sorghum grain (Bulletin 536, 1970, p.33). Soybean meal supplemented cows gained 31 lbs. each during 4 months while biuret-fed cows lost 15 lbs. each. Cows fed sorghum with biuret in a separate mineral mix (fed free choice) lost 62 lbs. each.
Keywords: Beef; Biuret; Soybean meal; Bluestem pasture; Birth weight; Weaning weight